A fluorescent benzo[g]isoquinoline-based HIF prolyl hydroxylase inhibitor for cellular imaging - Mayer, M; Fey, K; Heinze, E; Rainer Wick, C; Abboud, M; Yeh, T; Tumber, A; Orth, N; Schley, G; Buchholz, B; Clark, T; Schofield, C; et al. (Wiley, 2018)
Prolyl hydroxylation domain (PHD) enzymes catalyze the hydroxylation of the transcription factor hypoxia‐inducible factor (HIF) and serve as cellular oxygen sensors. HIF and the PHD enzymes regulate numerous potentially tissue‐protective target genes which can adapt cells to metabolic and ischemic stress. We describe a fluorescent PHD inhibitor (1‐chloro‐4‐hydroxybenzo[g]isoquinoline‐3‐carbonyl)glycine which is suited to fluorescence‐based detection assays and for monitoring PHD inhibitors in biological systems. In cell‐based assays, application of the fluorescent PHD inhibitor allowed co‐localization with a cellular PHD enzyme and led to live cell imaging of processes involved in cellular oxygen sensing.